Geosynthetic reinforced piled embankment modeling using discrete and continuum approaches. Issue 1 (February 2021) - Tran, Quoc Anh; Villard, Pascal; Dias, Daniel
Abstract: Understanding the load transfer mechanism can support engineers having more economical design of geosynthetic reinforced piled embankments. This study aims to investigate the load transfer mechanisms by two different numerical methods including the Discrete Element Method (DEM) and the Finite Difference Method (FDM). The DEM model adopts (a) discrete particles to simulate the micro-structure of the granular materials and (b) coupled discrete element – finite element method (DEM-FEM) to capture the interaction between granular materials and geotextiles. On the other hand, the FDM model uses an advanced constitutive soil model considering the hardening and softening behaviour of the granular materials. The numerical results show that the geotextiles can only contribute to the vertical loading resistance in cases where the soils between piles are soft enough. In terms of design, an optimum value of the geotextile tensile stiffness can be found considering the load, the soft soil stiffness and the thickness of the embankment. Both the DEM and the FDM show that a high geotextile tensile stiffness is not required since an extra stiffness will slightly contribute to the efficiency of the geosynthetic reinforced piled embankments. Nevertheless, both models are useful to optimize the design of geosynthetic reinforced piled embankments. Highlights: Load transfer mechanisms Investigation using Discrete Element and Finite Difference methods. 3D numerical modeling of piled embankment systems. Geogrid element should be used when the membrane effect is present. Geotextile only contribute to the vertical resistance when its deflection is large enough. The optimal value of the geotextile tensile stiffness is approximately 1000 kN/m.